Biodegradable geotextiles – An overview of existing and potential materials. Issue 1 (February 2019) - Prambauer, M.; Wendeler, C.; Weitzenböck, J.; Burgstaller, C.
Abstract: Geotextiles are a group of mostly thermoplastic polymers, which are processed to flexible material sheets, and are installed on various landscapes for reinforcing or protective purposes. Most applied materials in the field are non-degradable polymers, such as polyolefins or polyesters, which can implicate environmental problems concerning soil pollution and accumulation of micro plastics. Because of these drawbacks, for some applications time-consuming re-collection of the material becomes necessary. Hence, the development of more environmentally friendly and biodegradable geotextiles is of interest for several application purposes. In this review biodegradable alternatives to the conventional polymeric geotextile fibers are discussed. In general, there are two material classes available, which are natural fibers and biodegradable polymers. While there is already quite a number of natural-fiber-based geotextiles available on the market, the idea of applying industrial biopolymers for this purpose is relatively unexplored. Geotextile fabrics, made of plant fibers, represent a promising approach and were already successfully installed in several applications. However, the use of natural fibers also entails some limitations regarding water uptake and stability. Therefore, the potential use of a different material class, which comprises degradable, thermoplastic biopolymers, is discussed in this overview as well. There is only little information available on the use of these biopolymers in connection with geotextiles, thus their suitability regarding biodegradation, price and mechanical properties were evaluated.